Flatulence, Filth, and Urban Form: Do Primes for Hygiene Influence Perceptions of Urban Density?. (June 2022) - Hooper, Michael
This paper examines whether hygiene priming influences urban density perceptions. Research shows many perceptions are influenced by priming, an implicit memory effect wherein exposure to one stimulus affects response to another. This paper examines whether urban density perceptions are similarly malleable, particularly with respect to hygiene primes. The results, which may have considerable planning implications, suggest they are not. If density perceptions could be primed, this could open up an array of subconscious-oriented interventions to modify them. In contrast, if density perceptions are relatively stable, as this research suggests, it may mean efforts to modify density patterns will meet resistance.